A comparative signaling cost analysis of macro mobility scheme in NEMO (MM-NEMO) with mobility management protocol - Islam, Syaila; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Mohd. Ramli, Huda Adibah; Abdul Latif, Suhaimi; Hassan, Wan Haslina; Hasan, Mohammad Kamrul; Khalifa, Othman Omran (IOP Publishing Ltd., 2013)
NEMO BSP is an upgraded addition to Mobile IPv6 (MIPv6). As MIPv6 and its enhancements (i.e. HMIPv6) possess some limitations like higher handoff latency, packet loss, NEMO BSP also faces all these shortcomings by inheritance. Network Mobility (NEMO) is involved to handle the movement of Mobile Router (MR) and it’s Mobile Network Nodes (MNNs) during handoff. Hence it is essential to upgrade the performance of mobility management protocol to obtain continuous session connectivity with lower delay and packet loss in NEMO environment. The completion of handoff process in NEMO BSP usually takes longer period since MR needs to register its single primary care of address (CoA) with home network that may cause performance degradation of the applications running on Mobile Network Nodes. Moreover, when a change in point of attachment of the mobile network is accompanied by a sudden burst of signaling messages, "Signaling Storm" occurs which eventually results in temporary congestion, packet delays or even packet loss. This effect is particularly significant for wireless environment where a wireless link is not as steady as a wired link since bandwidth is relatively limited in wireless link. Hence, providing continuous Internet connection without any interruption through applying multihoming technique and route optimization mechanism in NEMO are becoming the center of attention to the current researchers. In this paper, we propose a handoff cost model to compare the signaling cost of MM-NEMO with NEMO Basic Support Protocol (NEMO BSP) and HMIPv6.The numerical results shows that the signaling cost for the MM-NEMO scheme is about 69.6 % less than the NEMO-BSP and HMIPv6.